Early trends and predictors of renal function following computed tomography-guided percutaneous cryoablation of a renal mass in patients with and without prior renal impairment - Staziaki, Pedro V. (Radiol Bras, 2020)
OBJECTIVE: To assess trends and predictors of the glomerular filtration rate (GFR) after renal mass cryoablation in patients with and without history of renal impairment. MATERIALS AND METHODS: This was a retrospective study of 39 patients who underwent computed tomography-guided percutaneous cryoablation of a renal mass, divided into two groups: those with prior renal impairment (PRI+); and those without prior renal impairment (PRI−). The GFR trend and the chronic kidney disease stage were evaluated at baseline, as well as at 1, 6, and 12 months after cryoablation. Predictors of GFR at 1 and 6 months were modeled with linear regression. RESULTS: In both groups, the mean GFR at 1 month and 6 months was significantly lower than at baseline (p < 0.001 and p = 0.01, respectively). Although the GFR was lower across all time points in the PRI+ group (−26.1; p < 0.001), the overall trend was not statistically different from that observed in the PRI− group (p = 0.89). Univariate analysis showed that the decline in GFR at 1 and 6 months correlated with the baseline GFR (0.77 and 0.63; p < 0.001 and p = 0.03, respectively) and with the size of the ablation zone (−7.6 and −12.84, respectively; p = 0.03 for both). However, in the multivariate model, baseline GFR was predictive only of GFR at 1 month (p < 0.001). CONCLUSION: The trend in GFR decline after cryoablation is similar for patients with and without a history of renal impairment. Baseline GFR predicts the mean GFR in the early post-cryoablation period.